Workshop on Strengthening and Implementing STEM-Based Coding with ARTEC Japan-WOW Singapore - PPSTEMI: School Dissemination - Syahmani, Syahmani; Mahardika, Andi Ichsan; Winarti, Atiek; Khairunnisa, Yasmine; Prasetyo, Yogo Dwi; Wiranda, Nurruddin; Dewantara, Dewi; Rusmansyah, Rusmansyah; Wati, Mustika; Putra, Aminuddin Prahatama; Purba, Harja Santana; Salam, Abdul; Fajriah, Noor; Saputra, Novan Alkaf Bahraini; Pamuji, Rizky; Khair, Muhammad Sa’duddien; Febriyanti, Emma Rosana; Alfianti, Dewi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Based on initial questionnaire data filled out by Mathematics and Natural Sciences teachers in Barito Kuala (Batola) Regency and Banjarmasin City, it was found that understanding and application of STEM Coding in schools is still low, so it is necessary to hold a STEM Coding community service workshop. This community service project aims to help participants develop critical thinking, creative, collaborative, and STEM literacy (4C) skills. The four stages of the community service method are planning, implementation, observation, and evaluation. A total of 127 teachers participated in the workshops. Speakers from PPSTEMI, Artec Japan, and WOW Singapore presented in the hybrid format event. The material consists of three modules: STEM-based learning, STEM Coding programming with Arduino Basic (Stop and Go), and Intermediate (Controlling a Motorized Car). Activities were evaluated using a response questionnaire, to which 127 people responded. The findings revealed that, on average, 95.47% of participants thought favorably of this STEM Coding exercise.Critical thinking, creativity, collaboration, and STEM literacy are among the skills that workshop attendees can acquire—wrapped up this STEM Coding workshop to help them become more STEM literate. Based on initial questionnaire data filled out by Mathematics and Natural Sciences teachers in Barito Kuala (Batola) Regency and Banjarmasin City, it was found that understanding and application of STEM Coding in schools is still low, so it is necessary to hold a STEM Coding community service workshop. This community service project aims to help participants develop critical thinking, creative, collaborative, and STEM literacy (4C) skills. The four stages of the community service method are planning, implementation, observation, and evaluation. A total of 127 teachers participated in the workshops. Speakers from PPSTEMI, Artec Japan, and WOW Singapore presented in the hybrid format event. The material consists of three modules: STEM-based learning, STEM Coding programming with Arduino Basic (Stop and Go), and Intermediate (Controlling a Motorized Car). Activities were evaluated using a response questionnaire, to which 127 people responded. The findings revealed that, on average, 95.47% of participants thought favorably of this STEM Coding exercise.Critical thinking, creativity, collaboration, and STEM literacy are among the skills that workshop attendees can acquire—wrapped up this STEM Coding workshop to help them become more STEM literate.